A proposed critical factor for effective implementation of quality engineering tools and techniques in Malaysian and Indonesian automotive industries - Nilda Tri Putri, author; Sha'ri Mohd. Yusof, author; International Graduate Conference on Engineering and Science (2008 : Johor) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL